KEUNGGULAN KOMPARATIF EKSPOR INDONESIA - suhardi suhardi; Afrizal Afrizal (LPPM STIE PERTIBA Pangkalpinang, 2021)
Export development is not only seen as an effort to increase state income but also to develop the national economy. Export development can also be used as one of the benchmarks for national economic development and the competitiveness of national products in the world market. In the period 1975-2020, the development of Indonesia's oil and gas and non-oil exports fluctuated but continued to experience a downward trend, this shows that Indonesia has fully entered into free global trade. The following graph shows the development of Indonesia's oil and gas and non-oil exports from 1975-2020. The partnership between countries that Indonesia is currently doing can accelerate the process of Indonesia's economic recovery. In the era of the global free market, if Indonesian products are not able to compete, then the openness of this market has no benefit for national industrial products so that comparative advantage is absolutely necessary for a product. Indonesia's five main sectors that have comparative advantages include automotive, textile and clothing, food and beverage, chemicals, and electronics. The contribution of the industrial sector to GDP was 20.48%, of which 18.08% came from the non-oil and gas processing industry. The five sectors are divided into Commodities which are currently the mainstay of Indonesia, namely shrimp, coffee, palm oil, cocoa, rubber, TPT, footwear, electronics, automotive, and furniture.